Engineering adoptive T cell therapy to co-opt Fas ligand-mediated death signaling in ovarian cancer enhances therapeutic efficacy - Anderson, Kristin G; Oda, Shannon K; Bates, Breanna M; Burnett, Madison G; Magdalia Rodgers Suarez; Ruskin, Susan L; Greenberg, Philip D (bioRxiv, 2021)
Background: In the U.S., more than 50% of ovarian cancer patients die within 5 years of diagnosis, highlighting the need for innovations such as engineered T cell therapies. Mesothelin (Msln) is an attractive immunotherapy target for this cancer, as it is overexpressed by the tumor and contributes to malignant and invasive phenotypes, making antigen loss disadvantageous to the tumor. We previously showed that adoptively transferred T cells engineered to be Msln-specific (TCR1045) preferentially accumulate within established ovarian tumors, delay tumor growth and significantly prolong survival in the ID8VEGF mouse model. However, T cell persistence and anti-tumor activity were not sustained, and we and others have previously detected FasL in the tumor vasculature and the tumor microenvironment (TME) of human and murine ovarian cancers, which can induce apoptosis in infiltrating lymphocytes expressing Fas receptor (Fas). Methods: To concurrently overcome this mechanism for potential immune evasion and enhance T cell responses, we generated an immunomodulatory fusion protein (IFP) containing the Fas extracellular binding domain fused to a 4-1BB co-stimulatory domain, rather than the natural death domain. T cells engineered to express TCR1045 alone or in combination with the IFP were transferred into ID8VEGF-tumor bearing mice and evaluated for persistence, proliferation, anti-tumor cytokine production, and therapeutic efficacy. Results: Relative to T cells modified only to express TCR1045, T cells engineered to express both TCR1045 and a Fas IFP preferentially persisted in the TME of tumor-bearing mice due to improved T cell proliferation and survival. Moreover, adoptive immunotherapy with IFP+ T cells significantly prolonged survival in tumor-bearing mice, relative to TCR1045 T cells lacking the IFP. Conclusions: Fas/FasL signaling can mediate T cell death in the ovarian cancer microenvironment, as well as induce activation-induced cell death, an apoptotic mechanism responsible for regulating T cell expansion. Upregulation of FasL by tumor cells and tumor vasculature represents a mechanism for protecting growing tumors from attack by tumor-infiltrating lymphocytes. As many solid tumors overexpress FasL, an IFP that converts the Fas-mediated death signal into pro-survival and proliferative signals may provide an opportunity to enhance engineered adoptive T cell therapy against many malignancies. Competing Interest Statement P.D.G., and S.K.O. have patents with and P.D.G. was a scientific consultant for Juno Therapeutics.